2021
DOI: 10.3390/ijerph18168398
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Perceptions and Measures of Weather and Walking, United States—2015

Abstract: Introduction: Weather can be a barrier to walking. Understanding how perceptions of weather as a barrier and measured temperature are associated with walking can inform monitoring and promotion strategies. The objective of this study is to examine the association between perceptions of weather as a barrier to walking and measured weather with the volume of leisure and transportation walking. Methods: The 2015 National Health Interview Survey (NHIS) assessed participation in and volume of walking (transportatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Prior work has shown that environmental perceptions have just as large of an impact on health outcomes as actual environmental exposures. 32,33 This study innovatively incorporates the knowledge and perceptions of youth to develop an environmental health perspective theoretical framework.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior work has shown that environmental perceptions have just as large of an impact on health outcomes as actual environmental exposures. 32,33 This study innovatively incorporates the knowledge and perceptions of youth to develop an environmental health perspective theoretical framework.…”
Section: Discussionmentioning
confidence: 99%
“…Research has also highlighted the significant impact of environmental health sentiments on environmental health outcomes. 32,33 One study investigated the relationship between environmental exposures, perceptions, and outcomes for indoor and outdoor air quality in Seoul, Korea by collecting data and surveying 396 elementary school students (average age = 11) and 64 parents. 32 This study found that environmental health sentiments significantly influenced environmental health outcomes, even in areas with comparable environmental exposures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adverse weather conditions are associated with a higher mortality and morbidity risk rate in individuals with chronic health conditions [17]. This negative correlation has been observed in outcomes related to cardiovascular issues and other health concerns linked to high-or low-temperature weather conditions [18,19]. Therefore, gathering evidence on how weather affects physical activity levels is imperative, particularly for those with chronic health conditions, as the information can help individuals make informed decisions about their outdoor activities and enable healthcare professionals to provide more favorable and affordable prescriptions for outdoor exercise and as it is crucial for individuals with chronic health conditions to reach the recommended level of physical activity [20].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have investigated the correlation between weather conditions and physical activity behavior. Some studies have utilized self-reports to evaluate physical activity levels [18,21,22], while others have objectively assessed daily physical activity over a short period [23][24][25]. Therefore, the need for long-term, objectively measured physical activity assessments with different weather conditions is paramount to overcome the limitations created by self-reported bias.…”
Section: Introductionmentioning
confidence: 99%